2007
DOI: 10.1177/0047287507308331
|View full text |Cite
|
Sign up to set email alerts
|

The New Environmental Paradigm and Nature-Based Tourism Motivation

Abstract: This study examines the relationship between environmental attitudes as measured by the new environmental paradigm (NEP) and nature-based tourism (NBT) motivations based on data gathered from a national forest park in China. The results indicate that tourists' environmental attitudes are heterogeneous across all four tourism motivations. Specifically, those who are more supportive of limits to growth and who are more concerned about ecocrisis tend to have a higher desire to be close to nature, to learn about n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
240
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(270 citation statements)
references
References 51 publications
20
240
2
8
Order By: Relevance
“…This could further be tested, for example, in terms of different groups of volunteers categorized according to expressed environmental attitudes or relationship between different attitudes and participation in conservation volunteering. This part of our research was guided by studies of the relationship between environmental attitudes and pro-environmental behaviors which employed the NEP theory and our findings are in line with this past research (e.g., Eagles and Higgins 1998;Luo and Jinyang 2008;Sampaio et al 2012). Moreover, not only does it contribute to the explanation of what factors affect reception of pro-environmental promotional messages, but also it provokes further discussion of the relevance of environmental attitudes, and hedonic desires.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This could further be tested, for example, in terms of different groups of volunteers categorized according to expressed environmental attitudes or relationship between different attitudes and participation in conservation volunteering. This part of our research was guided by studies of the relationship between environmental attitudes and pro-environmental behaviors which employed the NEP theory and our findings are in line with this past research (e.g., Eagles and Higgins 1998;Luo and Jinyang 2008;Sampaio et al 2012). Moreover, not only does it contribute to the explanation of what factors affect reception of pro-environmental promotional messages, but also it provokes further discussion of the relevance of environmental attitudes, and hedonic desires.…”
Section: Discussionsupporting
confidence: 72%
“…Past research has applied the NEP scale mainly to predict various proenvironmental behaviors (e.g., Eagles and Higgins 1998;Luo and Jinyang 2008;Voluntas (2017) 28:288-306 293 Sampaio et al 2012). For instance, Eagles and Higgins (1998) demonstrated positive association between pro-environmental attitudes and one's engagement in pro-environmental behaviors.…”
Section: Conservation Volunteeringmentioning
confidence: 99%
“…Here, we used the new environmental paradigm (NEP), which is a conceptualized measure of people's environmental attitudes, beliefs and values, to measure people's environmental value orientation (Dunlap et al 2000;Ardahan 2012). Previous studies (Kaltenborn & Bjerke 2002;Rauwald & Moore 2002;Hunter & Rinner 2004;Berenguer et al 2005;Kaltenborn et al 2008;Luo & Deng 2008;Ardahan 2012) and conceptual and psychometric testing (Stern et al 1995;Pierce et al 1997) have shown that high NEP scores are correlated with pro-environmental values (Dunlap et al 2000). Low NEP scores are associated with anthropocentrism, where humans view nature solely as a source of food and water.…”
Section: Introductionmentioning
confidence: 99%
“…Hedlund, Marell, andGarling (2012) explain further that travelers who care about the environment will concern more with perceived sustainability of the nature in choosing a travel destination, which is also influenced by gender, education, age and income. Meanwhile, the description of goals, motivations and attitudes can be used to predict future behavior intentions and different attitudes of travelers visiting ecotourism sites (Lee 2009;Luo and Deng 2008;Wurzinger and Johansson 2006).…”
Section: Introductionmentioning
confidence: 99%